THE CONCEPT OF LEGALIZATION OF INCOME, CRIMINALLY OBTAINED - Kudratillaev Khazratali (Scholar Express Journals, 2023)
The article discusses the origin of the term "legalization (laundering) of proceeds from crime". The opinions of scientists regarding the content of this concept are given. The definitions given in the regulatory legal acts of the Russian Federation containing the concept of "legalization (laundering) of proceeds from crime" are considered. Based on the analysis of legislative definitions and doctrinal concepts, the author proposes his own definition of the concept of "money laundering".
Keywords: proceeds from crime; legalization; laundering; criminal proceeds;